What Do We Know About Taxpayer Responses to Tax Changes? - Carina Neisser (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
The classical trade-off between equity and efficiency is central to income tax policy. On the one hand, higher taxes imply more resources to redistribute; but on the other hand, they might negatively affect incentives to work and the reporting of income itself. The design of tax and transfer policies, therefore, requires estimating the magnitude of behavioural responses to tax rate changes. Roughly speaking, the larger the responses to taxation, the smaller optimal tax rates should be.
Keywords: 330